Pengaruh Kualitas Produk dan Brand Image terhadap Loyalitas Pelanggan: - Atika Ronaa; Siti Ning Farida (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This research is motivated by the large number of fashion industries in the shoe sector which creates a competition to attract and retain customers. This study aims to determine whether Product Quality and Brand Image have an effect on Customer Loyalty of Converse Shoes. The population used in this study were consumers of Converse Shoes at Pakuwon Trade Center Surabaya. The sample required is 100 respondents. The sampling technique used in this research is non-probability sampling. The type of data used in this study is primary data, namely data collected or obtained directly from the object of research. The data collection technique used in this study was a questionnaire with closed questions. The data analysis technique used in this research is multiple linear regression analysis. Thus, the results of this study that simultaneously and partially Product Quality and Brand Image have a significant effect on Converse Shoes Customer Loyalty. Keywords: Product Quality; Brand Image; Customer Loyalty